The Loom of Life Unravelling Ecosystems - Schilthuizen, Menno. (Springer Berlin Heidelberg, 2009)
How can thousands of tree species coexist in a patch of tropical rainforest where there seem to be just a handful of niches? Why does biodiversity boom at the equator and plummet at the poles? Questions like these are central to modern ecology, where the gap between the familiar "niche" and the staggering (but sharply decreasing) global biodiversity seems to become ever wider. This book helps students and the general reader to bridge that gap, by tip-toeing from the smallest to the largest ecosystems.